PENGARUH JUS BELIMBINGTERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA DI KELURAHAN TANJUNG PAKU WILAYAH KERJA PUSKESMAS TANJUNG PAKU KOTA SOLOK - Armanda Tri Murti Ningsih (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Hypertension is a state of increased blood pressure that will provide advanced symptoms for a target organ such as stroke (for brain), coronary heart disease (for heart blood vessels) and right ventricular hyper trophy / left ventricle hypertrophy (for the heart muscle). Hypertension treatment includes modern medicine (medicine) and traditional medicine. One of the traditional treatments is to consume starfruit juice. The purpose of this study was to look at the effect of star fruit juice on the reduction of blood pressure in patients with hypertension in Tanjung Paku Village, the working area of Tanjung Paku Kota Solok Health Center.This research was experimental by using the design of one group pretest and posttest. The population in this study were all hypertensive sufferers who had hypertension in the Tanjung Paku Subdistrict, amounting to 27 patients. Samples taken by using purposive sampling obtained a sample of 5 people. Retrieval of data to determine blood pressure using tension meters before giving star fruit juice and on day 3, which is 2 hours after administration of starfruit juice. Data analysis is done by T-test.The results of statistical tests with the T-test at pretest obtained a mean (mean) of 144 mmHg with a standardization of 5.48 and in the posttest the mean (mean) 132 mmHg with a standard mean of2.74. The T-test value was obtained significantly (2-tailed) by 0,000 (p